N15 Feedback from adolescents and parents on the transition process to an Irish Adult IBD service. (21st January 2022) - Hamzawi, M; Brannick, S; Hickey, Y; Jones, F; Brett Kilmurray, O; Sheridan, J; Cullen, G
Abstract: Background: A nurse-led service improvement project has implemented a structured MDT model of transition for adolescents transitioning their IBD care to adult service in a tertiary hospital over a two-year period. Guidelines recommend obtaining service user and carer/parent perspectives on the process and identifying when additional emotional and psychological support is required. This had not been completed to date by the service. Methods: Adolescents (13) and their parents/carer (7) who have been attending the service for 1 year were invited to complete a service-designed, patient experience questionnaire to determine how well they have adapted to adult services. Items from The Brief Illness Perception Questionnaire (B-IPQ) were used to measure how participants understand and are impacted by their IBD. Negative illness perceptions are associated with anxiety, depression and poor quality of life. Results: Of the 13 responses from adolescents 85% felt ready to leave children's services at time of transfer compared to 71% of the parents. 87% of parents had concerns re transfer compared to 31% of adolescents.92% of the adolescents felt they had a chance to talk about their concerns and would also be happy to individually contact the IBD nurses with questions. Only 23% would like the IBD nurses to contact parents directly for information/medical updates. A common theme in the open-ended questions for both the adolescents and parents was the change in responsibility with the questions being directly asked to the adolescent and they are now the point of contact for the service. The most common topics for more information were fatigue, stress, diet, and getting this from a website or individually were the preferred methods. When attending clinic appointments adolescents always want to see a doctor but would like the opportunity to meet with the IBD nurse, dietitian and psychologist when required and 85% would consider using an online self-booking system if available. 50%of the adolescents reported their IBD affected them emotionally and were concerned about their illness. Conclusion: Parents had greater concerns than their children regarding transition. Since moving to the adults services the adolescents attending can express their concerns and will independently contact the service. The service needs to consider providing more information about the topics requested and support in infusion services. The introduction to the IBD service of the patient information booklet, dedicated adolescent clinics, pre attendance MDT introduction meetings helped create a positive experience for the adolescents and parents. The MDT model of transition may help facilitate an individualised intervention pathway to address concerns and improve outcomes for this group.